STATE AUDIT IN THE SYSTEM OF ECONOMIC MANAGEMENT - Uspambaeva, M.K.; Rakaeva, A.N.; Аmrenova, G.K. (Academic Journal of Physical and Chemical Sciences, 2018)
The nature of modern management of structural economic transformations is that the problem of searching for effective economic methods, mechanisms and trajectories of managing the development of the country's potential comes to the fore. The system of public funds management, in which the state audit occupies a special place, as a strategic factor in the effective use of budget funds, as well as state property in general. This article discusses the role of public audit in the management of the economy of Kazakhstan. The analysis of control of the main economic directions of the state audit is carried out. The bodies of state audit management in the Republic are defined. The refined definition of the concept of state audit is given. The nature of state audit is described, efficiency of use of public funds, criteria and indicators of efficiency of activity of public authorities and also features of the organization and functioning of effective system of state audit are considered. The role and place of efficiency audit in the system of state financial control are specified. It is concluded that the system of state audit is one of the main conditions for effective management of budgetary funds and national resources, a priority factor in ensuring the financial security of the state.